Image reconstruction: An overview for clinicians. Issue 3 (25th June 2014) - Hansen, Michael S.; Kellman, Peter
<x xml:space="preserve">Abstract</x> Image reconstruction plays a critical role in the clinical use of magnetic resonance imaging (MRI). The MRI raw data is not acquired in image space and the role of the image reconstruction process is to transform the acquired raw data into images that can be interpreted clinically. This process involves multiple signal processing steps that each have an impact on the image quality. This review explains the basic terminology used for describing and quantifying image quality in terms of signal‐to‐noise ratio and point spread function. In this context, several commonly used image reconstruction components are discussed. The image reconstruction components covered include noise prewhitening for phased array data acquisition, interpolation needed to reconstruct square pixels, raw data filtering for reducing Gibbs ringing artifacts, Fourier transforms connecting the raw data with image space, and phased array coil combination. The treatment of phased array coils includes a general explanation of parallel imaging as a coil combination technique. The review is aimed at readers with no signal processing experience and should enable them to understand what role basic image reconstruction steps play in the formation of clinical images and how the resulting image quality is described. J. Magn. Reson. Imaging 2014. © 2014 Wiley Periodicals, Inc.J. Magn. Reson. Imaging 2015;41:573–585. © 2014 Wiley Periodicals, Inc.